Relationship Between Obstructive Sleep Apnea and Enuresis in Children: Current Perspectives and Beyond - Wang Z; Zhang P; Shi R; Yang S; Liu K; Zhou Z; Li Q (Nature and Science of Sleep)
Zhan Wang,1,* Pengpeng Zhang,2,* Run Shi,3,* Shuai Yang,1 Kui Liu,4 Zhaokai Zhou,1 Qi Li5 1Pediatric Urodynamic Center, Department of Urology, The First Affiliated Hospital of Zhengzhou University, Henan Joint International Pediatric Urodynamic Laboratory, Zhengzhou, 450052, People’s Republic of China; 2Department of Lung Cancer, Tianjin Lung Cancer Center, National Clinical Research Center for Cancer, Key Laboratory of Cancer Prevention and Therapy, Tianjin’s Clinical Research Center for Cancer, Tianjin Medical University Cancer Institute and Hospital, Tianjin, People’s Republic of China; 3Department of Oncology, The First Affiliated Hospital of Nanjing Medical University, Nanjing, People’s Republic of China; 4Department of Pediatric Surgery, The First Affiliated Hospital of Henan University of Science and Technology, Luoyang, 471000, People’s Republic of China; 5Department of Pediatric Surgery, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhaokai Zhou, Pediatric Urodynamic Center, Department of Urology, The First Affiliated Hospital of Zhengzhou University, Henan Joint International Pediatric Urodynamic Laboratory, Zhengzhou, 450052, People’s Republic of China, Email 13526278113@163.com Qi Li, Department of Pediatric Surgery, the First Affiliated Hospital of Zhengzhou University, Zhengzhou, 450052, People’s Republic of China, Email siloam1994@163.comBackground: Nocturnal enuresis (NE) and obstructive sleep apnea (OSA) are common diseases in children, which often cause various social and psychological problems. The coexistence of both seriously affects the physical and mental health of children. However, whether OSA can directly lead to NE and the specific pathogenesis is still unclear. Moreover, the benefits of surgical and non-surgical treatments for OSA on NE symptoms remain controversial. This review summarizes the relationship between NE and OSA and how to treat them, aiming to provide a reference for the clinical treatment of OSA and NE in children.Methods: All pertinent original publications to this point from PubMed database have been collected, including investigations on the connection between OSA and NE as well as studies on the mechanism and therapeutic strategy of NE in children with OSA.Results: There is a bidirectional relationship between OSA and NE in children. NE increases with the incidence of OSA, and children with NE often have sleep-disordered respiratory disease. Children with OSA may be susceptible to NE due to aberrant humoral factors secretion, sleep-wake disorder, bladder dysfunction, obesity, and psychosomatic factors. It has been suggested that adenotonsillectomy (AT) may be the best treatment option for children suffering from OSA with NE. The benefits of positive airway pressure (PAP) therapy in children with NE remain to be further studied.Conclusion: NE and OSA comorbidity seriously affect the physical and mental health of children. AT can benefit children with OSA and NE. A comprehensive multidisciplinary evaluation of children with NE and OSA is needed, and the mechanism and treatment of NE in children with OSA need to be further explored.Keywords: obstructive sleep apnea, nocturnal enuresis, children, atrial natriuretic peptide, sleep-wake disorder, adenotonsillectomy